Factor Analysis and Model of Intention to Adopt Induction Stove - Halim Qista Karima; Dina Rachmawaty; Ade Yanyan Ramdhani (Jurnal Ilmiah Teknik Industri, 2023)
Household dependency on Liquified Petroleum Gas (LPG) gas increased Indonesian LPG imports. Therefore, the government encourages the conversion of LPG to induction stoves. However, induction stove users are less than LPG users. LPG stoves, electric stoves, and induction have their advantages and disadvantages. Consumers have different behaviours/responses to each change because each consumer has a diverse/heterogeneous character. This study analyzes the factors influencing consumer intentions to adopt an induction stove. The method used in determining factor analysis is the Structure Equation Model (SEM). The SEM method can model a causal relationship with a complex problem and determine the percentage of influence. The analysis found that the intention to adopt an induction stove was significantly influenced by subjective norm (SN), perceived behaviour control (PBC), and attitude toward behaviour (ATT). PBC is affected considerably by Speed, Maintenance, Cost, and Product Safety. ATT is significantly affected by Speed, Cost, Maintenance, and Security. Alternative penetration policy can be carried out on product heating speed, cost, and product maintenance, which are the variables that most significantly influence the adoption of induction stoves.